2015
DOI: 10.3390/economies3040216
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic Economic Consequences of Healthcare Payments: Effects on Poverty Estimates in Egypt, Jordan, and Palestine

Abstract: Healthcare payments could drive households with no health insurance coverage into financial catastrophe, which might lead them to cut spending on necessities, sell assets, or use credit. In extreme cases, healthcare payments could have devastating consequences on the household economic status that would push them into extreme poverty. Using nationally representative surveys from three Arab countries, namely, Egypt, Jordan, and Palestine, this paper examines the incidence, intensity and distribution of catastro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 16 publications
(19 reference statements)
1
44
1
Order By: Relevance
“…It can be argued that one explanation for this may be lack of utilization by those in low‐income levels, so actually, they are excluded from the cycle of receiving services, and higher income households can use healthcare services, and consequently, they are more likely to face catastrophic health expenditures. This issue was also mentioned in a study conducted by Rashad et al in Egypt, Jordan, and Palestine . Results of a study in Malaysia showed that although urban households in Kuala Lumpur are richer than those in rural areas, they are at a higher rate of exposure to catastrophic expenditures resulted from hospitalization because of rotavirus gastroenteritis; this is because of the development of the desirable primary healthcare network in rural areas and the possibility for the utilization of healthcare services with lower direct and indirect costs for rural households, compared to urban households.…”
Section: Discussionmentioning
confidence: 91%
“…It can be argued that one explanation for this may be lack of utilization by those in low‐income levels, so actually, they are excluded from the cycle of receiving services, and higher income households can use healthcare services, and consequently, they are more likely to face catastrophic health expenditures. This issue was also mentioned in a study conducted by Rashad et al in Egypt, Jordan, and Palestine . Results of a study in Malaysia showed that although urban households in Kuala Lumpur are richer than those in rural areas, they are at a higher rate of exposure to catastrophic expenditures resulted from hospitalization because of rotavirus gastroenteritis; this is because of the development of the desirable primary healthcare network in rural areas and the possibility for the utilization of healthcare services with lower direct and indirect costs for rural households, compared to urban households.…”
Section: Discussionmentioning
confidence: 91%
“…The demand for maternity healthcare is mainly served by private health providers that require fees, as public health service is widely viewed as an inferior service. The reliance on private healthcare in Egypt was found to be pushing a substantial proportion of households into poverty and deprivation (Rashad & Sharaf, , ).…”
Section: Discussionmentioning
confidence: 99%
“…Achieving an equitable access to health care and protecting the poor from encountering catastrophic medical payments have been the key objectives of the Health Insurance Agency (HIA) that was developed in 1964. However, paying for medical care remains a major barrier for receiving health care, as HIA covers only 55 per cent of the Egyptians (Rashad & Sharaf, ).…”
Section: Introductionmentioning
confidence: 99%